Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
2, 0, -2, -4
Step-by-step explanation:
an = 4 − 2n
a1 = 4 - 2(1) = 2
a2 = 4 - 2(2) = 0
a3 = 4 - 2(3) = -2
a4 = 4 - 2(4) = -4
Answer:
(2, 0, -2, -4)
Step-by-step explanation:
a(1) = 4 - 2(1)
= 4 - 2
= 2
a(2) = 4 - 2(2)
= 4 - 4
= 0
a(3) = 4 - 2(3)
= 4 - 6
= -2
a(4) = 4 - 4(4)
= 4 - 8
= -4
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.